Multivariate analysis of five homoeopathic medicines in a psychiatric population - Davidson, Jonathan; Woodbury, Max; Morrison, Roger; Shore, Jonathan; Rshom, Greg Bedayn (British Homeopathic Journal, 1995)
Grade of Membership Analysis (GoM) is a multivariate statistical technique developed for the purposes of medical classification. It was applied to the drug picture concept of homoeopathy, assessing five common medicines with particular applicability to anxiety. These were Arsenicum album (Ars), Gelsemium (Gels), Argentum nitricum (Arg-n), Lycopodium (Lyc) and Sulphur (Sulph). The patient sample comprised 104 psychiatric outpatients with structured clinical interviewbased primary diagnoses of social phobia, panic disorder, post traumatic stress disorder, obsessive-compulsive disorder, major depression and dysthymia. A homoeopathic screening questionnaire (HSQ) was used to test the integrity of the five drug pictures. Four pure types emerged, providing some evidence to support distinctions between Sulph and Arg-n features, and a pure type with many features of Ars, Arg-n, Lyc and Gels. The fourth pure type contained few of the drug's characteristics. There was some evidence to suggest that psychiatric diagnoses assorted differentially, based on the homoeopathically determined pure types. This study provides qualified support for the drug picture descriptions.
Keywords: Anxiety; Questionnaire; Structured interview; Grade of membership analysis; Homoeopathic types